The role of fluoride on lesion formation and arrestment - JARDIM, Juliana Jobim (2005)
The dental mineral structure depends on the oral environment. Once expose to the oral medium, changes in temperature, buffer ca¬pacity and plaque pH can lead to the solubi¬ lization of the hydroxyapatite crystals. When pH values lower than 5.5 are reached, an increase in crystals solubility and dissolution is favored. However, if episodes of physiolo¬gical pH occur more often than episodes of low pH, there is a return to the state of equi¬librium between the ions from saliva and dental enamel. On the other hand, if low pH periods become more frequent, withdraw of ions from the tooth can take place, forming a lesion. The control of the de and reminerali¬zation processes imbalance, leading to the lesion arrestment, can be reached by altera¬tions on local factors, such as diet, oral hygi¬ene and use of fluoride. The understanding of the caries lesion formation and arrestment allows to diagnose earlier stages of mineral loss, along with establishment of measures to control the progression of the lesion. The aim of this paper is to review the role of fluoride on lesion formation and arrestment. The phe¬nomena occurring throughout lesion formati¬on and control will be described.